2019
DOI: 10.3390/educsci9030195
|View full text |Cite
|
Sign up to set email alerts
|

Film Students’ Attitude toward Open Educational Resources (OERs) for Film Studies in Greece

Abstract: Open Educational Resources (OERs) have become a very useful medium in the fields of education, research, and training in recent decades, supported by governments and highly respected universities and institutions worldwide. Today's university students-in western societies mainly-have been born and raised in a digital world; consuming, providing, and sharing information over the internet 24/7. In that respect, it is interesting to examine whether OERs are a type/kind of information that they would like to "cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…The results, through interactive teachings, revealed that the main purpose of the research has been achieved, while they are in accordance with the literature on provision of technology-enhanced learning through the use of audiovisual media technologies in education (see, for example, Chatzara et al 2019;Papadopoulou 2019;Tzima et al 2019), and especially in the field of media studies (see Georgiadou and Kolaxizis 2019;Matsiola et al 2019;Sidiropoulos et al 2019). It is apparent that this interactive teaching using audiovisual media technologies, which were enriched with multimodal content and material (e.g., podcasts, sound/audio media spots, etc.)…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results, through interactive teachings, revealed that the main purpose of the research has been achieved, while they are in accordance with the literature on provision of technology-enhanced learning through the use of audiovisual media technologies in education (see, for example, Chatzara et al 2019;Papadopoulou 2019;Tzima et al 2019), and especially in the field of media studies (see Georgiadou and Kolaxizis 2019;Matsiola et al 2019;Sidiropoulos et al 2019). It is apparent that this interactive teaching using audiovisual media technologies, which were enriched with multimodal content and material (e.g., podcasts, sound/audio media spots, etc.)…”
Section: Discussionsupporting
confidence: 86%
“…The use of audiovisual media technologies and audiovisual content (audiovisual media communications from here on) in education, and especially in the field of media studies (e.g., courses in journalism, radio, television, social media, public relations, communication, etc.) (see Georgiadou and Kolaxizis 2019;Matsiola et al 2019;Nicolaou et al 2019;Şardagı and Öztürk 2019;Quinn-Allan 2010), contributes to effective teaching, to technologyenhanced learning, and to the provision of easier acquired knowledge (Frolova et al 2020;Nicolaou 2019a;Nicolaou et al 2019;Ewing et al 2018). The triptych of information communication technologies (ICTs), which are the main backbone of the media (see Mbeke et al 2010;Schiffrin 2017), provide the kind of knowledge that creates a new modernized and digital age of experiences for each generation, respectively (Thurder 2021;Nicolaou and Kalliris 2020;Nicolaou et al 2019;Kim 2019;Edwards [2010] 2010) (something we will discuss below).…”
Section: Introductionmentioning
confidence: 99%
“…Open courseware (OCW), open textbooks and Massive Online Open Courses (MOOCs) can all be. OERs include complete courses, individual course units or modules, textbooks, lesson plans, syllabi, lectures, assignments, game-based learning programs, quizzes, podcasts videos, audios, interactive simulations, and interactive multimedia (Georgiadou & Kolaxizis, 2019). OERs can also be divided up by their content format, though most OERs will be composed of a variety of media: Textled, video-led, animation-led, and multiple media (Open Education Policy Network, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such views have deviated from the original meaning of the classical methodology of Marxist literary and artistic research in the specific interpretation ( Klevan, 2020 ). Georgiadou and Kolaxizis (2019) reasoned that investigating the problems in the film industry was based on the problems in education. Therefore, teaching reform could comprehensively improve the problems in the Cinematography teaching and the film industry ( Georgiadou and Kolaxizis, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… Georgiadou and Kolaxizis (2019) reasoned that investigating the problems in the film industry was based on the problems in education. Therefore, teaching reform could comprehensively improve the problems in the Cinematography teaching and the film industry ( Georgiadou and Kolaxizis, 2019 ). Graesser et al (2022) observed that in the recent 20 years, China’s Educational Psychology (EPSY) has been unprecedentedly prosperous.…”
Section: Introductionmentioning
confidence: 99%